(2625) Proposal to reject the name Littorella spicata (Plantaginaceae) - Hassemer, Gustavo (2018)
Littorella flexuosa Raf., New Fl. 4: 12-13. 1838 [incorrectly given as 1836], nom. rej. prop.Typus: non designatus. Littorella subgenus Xamotris Raf., New Fl. 4: 12. 1838 [incorrectly given as 1836], nom. rej. prop.Lectotypus (designated here): Littorella flexuosa Raf. In accordance to Art. 56.1, we believe that the best course of action would be to reject the name L. flexuosa, along with Littorella subgenus Xamotris, in order to prevent that a considerably dubious name threaten a well-stablished species name, causing a disadvantageous nomenclatural change.